Consumer perspectives on assistive technology outcomes. (25th January 2013) - Lenker, James A.; Harris, Frances; Taugher, Mary; Smith, Roger O.
Abstract: Purpose : The current study explored domains of assistive technology (AT) device outcomes that are most valued by AT users. A secondary objective was to identify elements in the device acquisition process that affect outcomes. Method : Focus groups were conducted at geographically dispersed locations within the USA. The groups were moderated by experienced AT practitioners who followed a detailed procedure emphasizing a nominal group facilitation technique. Results : Twenty-four adult AT users, representing a range of ages and disability populations, participated in four focus groups. Many had over 15 years of experience with multiple device types. Qualitative analysis yielded 13 threads that embodied salient outcome domains (e.g. independence, subjective well-being, participation in work and school, cost-effectiveness) and key factors associated with the device acquisition process (e.g. lengthy periods of frustration, variable quality of service providers). Ironically, these data were evoked only after the term "outcomes" was omitted from focus group questions. Conclusions : AT outcomes studies are needed that report data regarding (a) the impact of AT on participation, (b) costs of AT provision and (c) key elements in the AT service delivery process. Future studies will be further strengthened to the extent that their methodologies actively assimilate consumer perspectives. Implications for Rehabilitation: Consumers highly value the impact of AT devices on their independence, subjective well-being and participation in work and school. The process of acquiring assistive technology devices is often lengthy and frustrating for consumers. Future AT outcomes research should report descriptive data regarding service delivery processes, as well as long-term impacts for consumers. Practitioners and researchers should avoid the use of potentially confusing professional jargon when administering surveys to consumers.